2011
DOI: 10.1021/jo200075v
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic C−H to C−C Conversion: Synthesis of (−)-Cameroonan-7α-ol

Abstract: In the course of a synthesis of the tricyclic sesquiterpene (−)-cameroonan-7α-ol from the acyclic (+)-citronellal, seven aliphatic C-H bonds were converted to C-C bonds, and three rings and four new stereogenic centers were established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 50 publications
0
4
1
Order By: Relevance
“…These results were consistent with those obtained by Menut et al (1997), although some discrepancies were found. They consisted in a lower amount of presilphiperfolan-8-ol (6.5 %) and the absence of cameroonan-7-α-ol that is the major contributor to the strong woody and patchouli-like smell of the root oil (Taber and Nelson, 2011). Conversely, we did not find presilphiperfol-7(8)-ene that was characterized as a new compound by these authors.…”
Section: Chemical Composition Of the Essential Oilscontrasting
confidence: 76%
“…These results were consistent with those obtained by Menut et al (1997), although some discrepancies were found. They consisted in a lower amount of presilphiperfolan-8-ol (6.5 %) and the absence of cameroonan-7-α-ol that is the major contributor to the strong woody and patchouli-like smell of the root oil (Taber and Nelson, 2011). Conversely, we did not find presilphiperfol-7(8)-ene that was characterized as a new compound by these authors.…”
Section: Chemical Composition Of the Essential Oilscontrasting
confidence: 76%
“…Another noteworthy constituent occurring in the oil was ( E )-caryophyllene (6.3%). The cameroonan-7-α-l, is responsible for the patchouli-like smell of the root oil [ 52 ]. The reported composition was quite consistent with that previously reported by Menut et al [ 49 ] for root samples collected in Cameroon.…”
Section: Resultsmentioning
confidence: 99%
“…201 The red alga Laurencia dendroidea contains a silphiperfolane sesquiterpene with leishmanicidal activity. 123 The synthesis of (À)-cameroonan-7a-ol from (+)-citronellal has been achieved, 202 whilst (R)-limonene has been used as starting material in the synthesis of the angular triquinane system present in the sesquiterpenes norsilphiperfolanes and norcameroonanes. 203 Boledulins A-C 209-211 are three botryane sesquiterpenoids, which have been obtained from the basidiomycete Boletus edulis.…”
Section: Chamigrane and Thujopsanementioning
confidence: 99%